Character Strengthening Strategies for Indonesian Students in the Digital Era: Literature Review - Mumthaza, Silwana; Cholily, Yus Mochamad; Pantiwati, Yuni; Rahardjanto, Abdulkadir (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
Indonesia faces a persistent character challenge in its education system, reflected in bullying and declining student well-being. Although character education is a national priority, evidence on practical approaches remains fragmented. This study synthesises research on character-strengthening approaches for Indonesian school students and maps the research landscape in the digital era. We conducted a systematic literature review following PRISMA guidelines and used the PICOS framework to define eligibility and guide screening. We searched Scopus for studies published between 2015 and 2025. The included studies (n = 33) were synthesised descriptively, and bibliometric patterns were visualised using VOSviewer. The synthesis indicates that the literature consistently emphasises collaboration and holistic learning as foundations for character development, often integrating local wisdom and religious values. Frequently discussed approaches include project-based learning, positive school culture initiatives, and school–family–community partnerships. However, implementation is repeatedly described as constrained by gaps between policy and classroom practice, limited teacher capacity, and weak school ecosystems, especially under pressures from digital environments.  Overall, character strengthening in Indonesia is best understood as an ecosystem effort that requires coordinated roles across schools, families, and communities. We recommend strengthening teacher capacity for integrative pedagogy, embedding collaborative values in daily learning, and developing sustainable evaluation mechanisms to monitor character outcomes.